Soils of the Mesters vig District, Northeast Greenland. 2.: Exclusive of Arctic Brown and Podzol-like Soils. - Ugolini, F. C. (Meddelelser om Grønland, 1966)
Different investigators have classified the soils of the Arctic according to genetic, morphologic, genetic-cryopedogenic, and cryopedogenic concepts. Instead of adhering to a specific classification, the soils of Mesters Vig are described and discussed, using terms already introduced in the literature. These soils include Lithosols, Arctic Brown soils, Podzol-like soils, Meadow and Upland Tundra soils, Tundra variant soils (soils of the gelifluction slopes, soils associated with certain patterned ground features, and soils associated with turf-hummocks), Protoranker soils, and Tundra Ranker soils. A single profile description is given for each one of these soils together with a discussion of the factors affecting the soil morphological properties. The cryopedogenic and gelifluction processes are very important factors affecting the morphology and the occurrence of the different typos of soils. Certain megascopic properties such as structure may be indicative of the stability of the soils on slopes, while miniature and shallow profiles in a patterned ground may provide some information on the activity of the cryopedogenic processes. The soils associated with patterned ground may undergo a dynamic evolution because the internal soils properties may be progressively changed by the cryopedogenic processes. Because the arctic soils are shallow and not well developed, they are very sensitive to small climatic changes and to other disturbances. Soil distribution and development reflect, therefore, the dynamic effect of arctic landscape.